2014
DOI: 10.1155/2014/185035
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of FOXO3, MYD88, and GAPDH Identified by Suppression Subtractive Hybridization in Esophageal Cancer Is Associated with Autophagy

Abstract: To find genes involved in tumorigenesis and the development of esophageal cancer, the suppression subtractive hybridization (SSH) method was used to identify genes that are overexpressed in esophageal cancer tissues compared to normal esophageal tissues. In our SSH library, the forkhead box O3 (FOXO3), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and myeloid differentiation primary response 88 (MYD88) genes were the most highly upregulated genes, and they were selected for further studies because of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…They believe that the use of GAPDH to negatively regulate tumor growth may be a new anti-cancer strategy [41,42]. They believe that the use of GAPDH to negatively regulate tumor growth may be a new anti-cancer strategy [43][44][45]. Yamaji et al reported that GAPDH is secreted by some cancer cells and can inhibit cell proliferation [46].…”
Section: Discussionmentioning
confidence: 99%
“…They believe that the use of GAPDH to negatively regulate tumor growth may be a new anti-cancer strategy [41,42]. They believe that the use of GAPDH to negatively regulate tumor growth may be a new anti-cancer strategy [43][44][45]. Yamaji et al reported that GAPDH is secreted by some cancer cells and can inhibit cell proliferation [46].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in FOXO3 expression induce autophagy [12]. Previous studies have shown that FOXO3 is closely related to tumourigenesis and is considered a tumour suppressor [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this general cellular function, GAPDH is supposed to be ubiquitously expressed [ 97 , 98 ] and is therefore commonly used as an housekeeping gene for internal control in protein samples loaded on western blots or for quantitative analysis of mRNA expression using PCRs. However, its function is much more complex and diverse than it was previously thought and GAPDH could no longer be considered as a good internal control for multiple cell normalization because of its over-expression in some models [ 99 , 100 , 101 ]. Excellent reviews are already published on the various GAPDH functions [ 102 , 103 , 104 , 105 ] with increasing knowledge on either neurodegenerative diseases [ 106 , 107 , 108 ] or cancer implication [ 109 , 110 , 111 , 112 , 113 ].…”
Section: Glyceraldehyde-3-phosphate Dehydrogenase (Gapdh) Binding mentioning
confidence: 99%